Grand societal challenges in information systems research and education : ideas from the ERCIS Virtual Seminar Series /: ideas from the ERCIS Virtual Seminar Series. (2015) - Brocke, Jan vom; Stein, Armin; Hofmann, Sara; Tumbas, Sanja
No abstract available